Effects of an Aboriginal Cultural Enrichment Program on Adolescent Mothers’ Self-Perceptions - Bent, Kathy; Josephson, Wendy; Kelly, Barry (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2004)
This study explored the effects of an Aboriginal cultural enrichment initiative on the self-concept of ten pregnant or parenting adolescent women, all but one of whom were of Aboriginal descent. The cultural enrichment activities were integrated into a program of support for adolescent mothers. Questionnaires were administered to the participants at the beginning and after six weeks of participating in the cultural enrichment component of the program. The Self-Perception Proﬁle for Adolescents (Harter, 1988) was used to measure global self-worth and self-perception across eight domains. Overall cultural identity, cultural identity achievement, cultural behaviours and sense of afﬁrmation and belonging were measured using the 20 item Multigroup Ethnic Identity Questionnaire (Phinney, 1998b). Individual audio-taped interviews were also undertaken following completion of the post-tests. After six weeks of the cultural enrichment program, the participants’ cultural identity achievement scores increased signiﬁcantly, and participants who had achieved a strong cultural identity also had higher levels of global selfworth. Average self concept became more positive in the speciﬁc domains of job competence and behavioural conduct. In the interviews, participants expressed positive reactions to the cultural component of the program, and attributed positive personal changes to the cultural experiences it provided. The results support the conclusion that it is highly beneﬁcial to incorporate a cultural component into services for Aboriginal youth.